(untitled) (Journal of Guidance and Counselling Studies, 2024)
Apart from medical treatment and facilities, the individuals need to be provided with health care counseling. It was shown that, counseling education focuses upon in imparting information in terms of ways of promoting good health and well-being of an individual and the family at large. Furthermore, it focuses on ways to prevent the occurrence of family health problems, illnesses and promoting healthy lifestyles. Counseling education for family healthcare takes place simultaneously with medical treatment. When medical practitioners and health care specialists are providing treatment to health problems and illnesses, they need to provide counseling as well. Counseling in terms of health care is considered important in the case of physical as well as psychological health. The important measures to promote health care counseling are, conducting analysis of areas, augmenting one’s knowledge, improving communication skills, implementing listening skills, implementing anti-discrimination policies, concentrating on facts, focusing on personality traits of counselees, focusing on reflection, practicing rephrasing and summarising and writing. The areas requiring the implementation of health care counseling are in terms of promoting good health, preventing diseases and health problems, curbing psychological problems, promoting healthy mind-sets and promoting healthy lifestyles. Finally, it can be stated that, counseling education contributes significantly in making provision of knowledge and understanding to the individuals in promoting good health and well-being. There is need to be ensured that counseling is suitable to the individuals. The medical practitioners, health care specialists and professional counselors need to make use of innovative methods in counseling sessions.